Antibiotic export by MexB multidrug efflux transporter is allosterically controlled by a MexA-OprM chaperone-like complex - Marie Glavier (Nature Portfolio, 2020)
The tripartite multidrug efflux system MexAB-OprM is a major actor in Pseudomonas aeruginosa antibiotic resistance by exporting a large variety of antimicrobial compounds. Here authors present cryo-EM structures of MexB at various stages of the assembly process and provide evidence that MexB activation is mediated by OprM and MexA.